2008
DOI: 10.1111/j.1937-8327.2006.tb00385.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Development Toward Instructional Design Expertise

Abstract: F or decades now, researchers have been investigating the nature of process and product in the practice of instructional design (ID). There are various useful descriptions of good ID and prescriptions for how ID should proceed. Both researchers and practitioners have generated rubrics and heuristics designed to assess ID deliverables as well as the design process. Graduate programs in institutions of higher education designed to cultivate the design skills of students typically include courses in ID with stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 30 publications
3
75
0
Order By: Relevance
“…Then they became aware of some processes continuing step by step, however most of them challenged to elaborate the previous step to the next step. This result is exactly similar with the results revealed in Hardre, Ge and Thomas (2006) in which authors explored that novice instructional designers treated the phases of ID like very different parts while after getting experienced they started to look ID phases as holistic process (p. 81). Moreover, they revealed that perception of responsibilities of instructional designers and metacognitive skills influence to expertise ID.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Then they became aware of some processes continuing step by step, however most of them challenged to elaborate the previous step to the next step. This result is exactly similar with the results revealed in Hardre, Ge and Thomas (2006) in which authors explored that novice instructional designers treated the phases of ID like very different parts while after getting experienced they started to look ID phases as holistic process (p. 81). Moreover, they revealed that perception of responsibilities of instructional designers and metacognitive skills influence to expertise ID.…”
Section: Discussionsupporting
confidence: 81%
“…As a design based learning environment, by means of multimedia design technical skills (Kafai, 1995), collaborative working skills (Gifford & Enyedy, 1999) and knowledge of subject matter (Kafai, 1995;Barron et al 1998) can be obtained. Hardre, Ge and Thomas (2006)'s case study showed that when a novice instructional designer designs a learning material, they might get more selfawareness, self-monitoring skills, clear understanding of IDT practices. Besides, novices might understand the expected competencies and learn how to improve their current knowledge to reach the goals of the field.…”
Section: Multimedia Design As a Context Of Training Instructional Desmentioning
confidence: 99%
“…This may be in part due to the participant group, which unlike many previous studies, were not teachers but professional design students. Building on previous research (e.g., Hardré, Ge & Thomas, 2007), it added more detailed assessments of perceptions, and revealed a cluster of perceptions that apparently position learners for a greater success in learning ID. Beyond confirming previous findings (generally from single-semester studies; e.g., Hardré, Ge & Thomas, 2007), this design extends the timeline of development to two semesters, enabling systematic assessment and analysis over a longer developmental trajectory.…”
Section: Contribution To the Field Of Idmentioning
confidence: 99%
“…A few studies have investigated learning and development of ID knowledge and skill among students of ID (Ertmer & Cennamo, 1995;Ge & Hardré, 2010;Hardré, Ge & Thomas, 2007;Quinn, 1994), and of designers in specialised contexts (e.g., Christensen & Ogusthorpe, 2004;Rowland, 1991). Some research has also been done on graduate teaching assistants learning ID as a strategic skill for transfer to their own professional teaching practice (Hardré & Chen, 2005).…”
Section: Id Learning and Skill Developmentmentioning
confidence: 99%
See 1 more Smart Citation